Forecasting Policy Pelayanan Sektor Publik Pasca Pemindahan Ibukota Negara: Studi Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu (DPMPTSP) DKI Jakarta - Hanandy, Rizka; Sakapurnama, Eko (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2024)
This article aims to provide a forecasting policy for the relocation of the National Capital and the existence of the Draft Law (RUU) for the Special Region of Jakarta (DKJ) on public sector services in Jakarta. Using a case study at the Jakarta Investment and One-Stop Integrated Services (DPMPTSP), this research uses William N. Dunn's (2018) policy forecasting framework and Menezes et al. (2022) public service assessment indicators to forecast future public services. Different from previous forecasting policy research, this study uses a comprehensive operationalization concept with a mix of a forecasting policy framework and public service assessment indicators. A qualitative approach was used in data collection and analysis through document study, secondary data, and literature review. The research results show that based on current conditions, DPMPTSP Jakarta is projected to provide optimal public services in the future, particularly regarding service quality and user satisfaction. However, on the other hand, the challenges faced are also increasingly complex, especially in optimizing the user's experience and providing an integrated database, especially between relevant sectoral agencies.